Sustainable Livelihoods and the Right of Access to Food: Achieving the National Development Plan 2030 Goals on Poverty Eradication - Mbajiorgu, Grace (Southern African Public Law, 2021)
Poor and marginalised households often lack the basic resources and assets that would enable them to cope with shocks such as unemployment, droughts and illness, and stressors such as distorted economic policies, illiteracy and landlessness. As a result, these households suffer severe poverty and food insecurity and without government intervention, they are vulnerable to a perpetual state of deprivation. Against this background, this article examines the relevance and importance of the concept of sustainable livelihoods in promoting access to food, with specific reference to the goal of the National Development Plan 2030 (NDP 2030) to eradicate poverty. The strategies aimed at poverty eradication as proposed in the NDP 2030 are discussed in relation to the sustainable livelihood approach or capabilities approach as developed in international law. First, this article discusses the origin and development of the notion of sustainable livelihoods as advanced by international instruments central to socioeconomic development and various scholars. The potentials and shortcomings of the sustainable livelihood approach are also examined. Second, livelihood assets in the form of land and policy are examined to determine their significance in promoting access to food. Finally, a conclusion is drawn on the integral role of the sustainable livelihood approach in enhancing livelihood security and assisting households to adopt both coping and adaptive strategies aimed at reducing poverty and food insecurity.